A Retrospective Study of Capecitabine/Temozolomide (CAPTEM) Regimen in the Treatment of Metastatic Pancreatic Neuroendocrine Tumors (pNETs) after Failing Previous Therapy - Saif, Muhammad Wasif; Kaley, Kristin; Brennan, Marianne; Garcon, Marie Carmel; Rodriguez, Gladys; Rodriguez, Teresa (JOP. Journal of the Pancreas, 2013)
Context Pancreatic neuroendocrine tumors (pNETs) are notoriously resistant to currently available chemotherapy agents. Preclinical data has suggested synergy between temozolomide and capecitabine. Objective To report a retrospective data on the efficacy and safety of capecitabine and temozolomide (CAPTEM regimen) in patients with metastatic pancreatic neuroendocrine tumors (pNETs) who have failed prior therapies. Methods We reviewed the medical records of 7 patients with metastatic pNETs who had had progressive cancer prior to treatment despite therapy, including long-acting release octreotide (60 mg/month), chemotherapy and hepatic chemoembolization. Capecitabine was administered at a flat dose of 1,000 mg orally twice daily on days 1-14 and temozolomide 200 mg/m2 was given in two divided doses daily on days 10-14 of a 28-day cycle. Tumor assessments were repeated every two cycles and serum tumor markers were measured every cycle. Response to treatment was assessed using Response Evaluation Criteria in Solid Tumors (RECIST) parameters, and toxicity was graded using the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE), version 3.0. Results Among 7 patients treated, three patients achieved a partial response, and two patients had stable disease. Total response rate was 43%, and clinical benefit (responders and stable disease) was 71%. Median duration of response was 8 months (range: 4-12 months). Grade 3 and 4 toxicities included grade 3 thrombocytopenia in one patient and grade 3 fatigue in one patient. The most common toxicities were grade 1 and 2 neutropenia, grade 1 fatigue, grade 1 and 2 hand-foot syndrome. Conclusions Our retrospective study showed that modified CAPTEM regimen was well-tolerated and produced comparable response to historical data in neuroendocrine tumors, including pNETs. Our study is unique as it only included patients with pNETs. Further prospective studies are warranted to evaluate the combination of CAPTEM regimen with targeted therapies in pNETs. Image: Schema of CAPTEM regimen.